DIGITAL TRANSCENDENT LEADERSHIP: A GROUNDED STUDY ON MADRASAH PRINCIPALS’ STRATEGIC AGILITY IN NAVIGATING THE MERDEKA CURRICULUM - Mus Mulyadi; Saifaldin Idris Onia (PEDAGOGIK : JURNAL PENDIDIKAN, 2026)
This study explores the emergence of Digital Transcendent Leadership (DTL) as a novel paradigm for navigating the complexities of the Merdeka (Emancipated) Curriculum within Islamic formal schools (Madrasahs). Employing a Constructivist Grounded Theory approach involving twelve Madrasah principals across Indonesia, the research reveals that strategic agility in faith-based educational contexts is not merely a technical proficiency but a deeply anchored metacognitive process rooted in transcendence. The findings construct the core category of the "Digital-Mursyid," a leadership model that synthesizes technological sophistication (high-tech) with spiritual depth (high-soul). Through the dimension of "Spiritualized Digitalization," leaders transform administrative burdens into forms of theological stewardship (Amanah) and utilize "Cultural Synthesis" to harmonize global digital standards with traditional ethical values (Adab). Theoretically, this research contributes to the decolonization of digital leadership by demonstrating that spiritual stability serves as the primary engine for ethical and agile innovation. Practically, the DTL model offers a theoretical roadmap for educational leaders to remain technologically progressive without compromising their foundational value systems.